Vegetation diversity, biomass, and carbon storage in post-burned lowland forest of Sangatta, East Kutai, East Kalimantan - Mariana Takandjandji; N. M. Heriyanto (Jurnal Penelitian Kehutanan Wallacea, 2022)
Forest fires can reduce biomass, carbon storage, and vegetation diversity. This research aims to obtain information on vegetation diversity, biomass, carbon content, and carbon dioxide equivalent in two lowland forests of Sangatta (East Kutai) that experienced forest fire in 2015 and 2017. The research was conducted in May 2019 by establishing one plot of 100m x 100m in 2015 and 2017 burned forests, respectively, and placed purposively in each site. The plots were divided into 25 sub-plots of 20m x 20m. All trees and saplings within its respected plots were identified and measured, including their DBH and height, while seedlings were identified and counted. The results showed that in 2015 burned forest contained 103 species and 38 families, including 59 species of trees (DBH ≥10cm) from 467 individuals. Meanwhile, in 2017 burned forest, we found 87 species and 36 families, including 69 species of trees from 398 individuals. We also found that three dominants species in 2015 burned forest were Macaranga gigantea with a density of 120 trees/ha or carbon sinks of 25.84 C kg, Melicope lunuankenda with a density of 63 trees/ha or 6.56 C kg, and Shorea seminis with a density/ha of 6 trees or 0.93 C kg. While three dominants species in 2017 burned forest were Alpitonia incana with a density of 165 trees/ha or carbon sinks of 6.87 C kg, Macaranga gigantea with a density of 60 trees/ha or carbon sinks of 6.18 C kg, and Callicarpa pentandra with a density/ha of 43 trees or 2.75 C kg. The estimated biomass, carbon content, and carbon dioxide equivalent in the burned forest in 2015 with a diameter ≥10cm were 102.20 tons/ha, 47.94 tons C/ha, and 175.94 tons CO2 eq/ha, respectively. Meanwhile, biomass, carbon content, and carbon dioxide equivalent in the burned forest in 2017 with a diameter of ≥10cm were 56.56 tons/ha, 26.58 tons C/ha, and 97.56 tons CO2 eq/ha, respectively.